Two cellular models for analyzing mitochondrial heteroplasmy - Yaning Hu; Lin Jiang; Wen Liu; Xingbo Zhao (Exploration of Neuroscience)
Aim: Mitochondria are essential for brain development, and the presence of different mitochondrial types is called mitochondrial heteroplasmy. Mitochondrial dysfunction is a central aspect of many people’s neurological diseases. Heteroplasmy is commonly observed in eukaryotes due to mitochondrial genome (mtDNA) mutation, paternal leakage, mitochondria transplantation/mitotherapy, and somatic cell nuclear transfer (SCNT). In this study, we developed two novel approaches to construct mitochondrial heteroplasmy cellular models. Methods: Model 1: the yak cell line (Bos grunniens) was transfected with p-eGFP-neo plasmid while mammary alveolar cell-T (MAC-T) cell line from cattle cells (Bos taurus) was stained with MitoTracker Deep Red FM. The yak cell line was used as recipient cells which fused with enucleated cattle cells. Model 2: The cattle cell line was stained with MitoTracker Green FM while yak cells were stained with MitoTracker Deep Red FM. Cattle cells were used as recipient cells which fused with enucleated yak cells. Following fusions, the single cells exhibiting dual positive fluorescence signals were sorted into 96-well plate by fluorescence-activated cell sorting. Confocal fluorescence examination confirmed that the cells with mitochondrial heteroplasmy were sorted. Results: The two methods can generate a variety of mitochondrial heteroplasmy cells of interest which can aid in understanding the patterns and influencing factors underlying heteroplasmy changes. Conclusions: The mitochondrial heteroplasmy cellular model contributes to managing heteroplasmy mitochondrial changes and preventing the development of mitochondrial declines.